ACEH PEOPLE'S BEDTIME CHILDREN TRADITION: Values and Messages Contained in Dodaidi's Poetry - Putri Wulandari, Alisa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Each region and tribe has its own traditions, just as in Aceh, there is a custom for people to put their children to sleep by singing Dodaidi poetry. In various literatures, it is explained that the custom of the people of Aceh to sing Dodaidi poetry is a legacy from their ancestors, which aims to teach Islamic religious values. In Muslim society it is believed that young children have good hearing and memory abilities, so various occasions, including when they sleep, are an opportunity to teach religious values. Based on this background, this research was conducted to analyze the values ​​and messages contained in Dodaidi's poetry as a bedtime for children. To answer this goal, a scientific method was established in the form of a qualitative approach using a literature review research method. The object of this research is the Dodaidi poetry of the people of Aceh, Indonesia. The results of the study reveal that Islamic religious values ​​are the main feature in Dodaidi's poetry, it contains deep messages for the life of the child as an adult, for example growing into a healthy and strong child so that he can defend his religion and country.